2000
DOI: 10.1152/jappl.2000.88.6.2219
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AMP-activated protein kinase increases mitochondrial enzymes in skeletal muscle

Abstract: Muscle contraction causes an increase in activity of 5'-AMP-activated protein kinase (AMPK). This study was designed to determine whether chronic chemical activation of AMPK will increase mitochondrial enzymes, GLUT-4, and hexokinase in different types of skeletal muscle of resting rats. In acute studies, rats were subcutaneously injected with either 5-aminoimidazole-4-carboxamide-1-beta-D-ribofuranoside (AICAR; 1 mg/g body wt) in 0.9% NaCl or with 0.9% NaCl alone and were then anesthetized for collection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
522
10
11

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 647 publications
(578 citation statements)
references
References 36 publications
35
522
10
11
Order By: Relevance
“…This is an important finding, in view of the fact that long-term exposure to other AMPK activators, such as AICAR, produces a moderate increase in the liver weight of animals [35,36] that has been considered a potential side-effect of this kind of molecule, and which has not been observed in the chronic treatment with resveratrol.…”
Section: Discussionmentioning
confidence: 80%
“…This is an important finding, in view of the fact that long-term exposure to other AMPK activators, such as AICAR, produces a moderate increase in the liver weight of animals [35,36] that has been considered a potential side-effect of this kind of molecule, and which has not been observed in the chronic treatment with resveratrol.…”
Section: Discussionmentioning
confidence: 80%
“…Several studies have shown that 5-aminoimidazole-4-carboxamide-1-β-D-ribofuranoside (AICAR), an AMPK activator, activates glucose transport and increases the expression of glucose transporter 4 (GLUT4) and several metabolic enzymes in skeletal muscle (Buhl et al, 2001;Holmes et al, 1999Holmes et al, , 2005Ojuka et al, 2002;Stoppani et al, 2002;Winder et al, 2000;Zheng et al, 2001). It has been reported that an increase in glucose uptake induced by AICAR results in increased lactic acid production in isolated rat skeletal muscle (Miyamoto et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, by virtue of its actions on these enzymes, AMPK activation would both increase the oxidation of fatty acids and diminish their esterification to form triglycerides and other glycerolipids. Furthermore, increases in AMPK activity caused by administering the AMPK activator, 5-aminoimidazole-4-carboxamide-1-β-D-ribofuranoside (AICAR), are associated with anti-obesity [19,20] and insulin-sensitising effects [21,22,23] and genetically mediated increases in uncoupling proteins [24,25] in rodents.…”
Section: Introductionmentioning
confidence: 99%